Microwave ablation induces abscopal effect via enhanced systemic antitumor immunity in colorectal cancer - Yu, Lu; Xie, Hairong; Wang, Linping; Cheng, Min; Liu, Jie; Xu, Jiamei; Wei, Zhigang; Ye, Xin; Xie, Qi; Liang, Jing (Frontiers in Oncology, 2023)
Background: Thermal ablation is the main method for local treatment of lung metastases. It has been known that radiotherapy and cryoablation can induce an abscopal effect, whilst the occurrence of abscopal effect induced by microwave ablation is a less, thus cellular and molecular mechanisms involved in the abscopal effect after microwave ablation should be further clarified. Methods: CT26 tumor-bearing Balb/c mice were treated with microwave ablation with different combinations of ablation power and time duration. The growth of primary or abscopal tumors and the survival of mice were both monitored, in addition, immune profiles in abscopal tumor, spleen, and lymph node were evaluated by flow cytometry. Results: Microwave ablation inhibited tumor growth in both primary and abscopal tumors. Both local and systemic T-cell responses were induced by microwave ablation. Moreover, the mice presenting significant abscopal effect after microwave ablation markedly increased Th1 cell proportion both in abscopal tumor and spleen. Conclusions: Microwave ablation at 3 w-3 min not only inhibited tumor growth in primary tumor, but also induced an abscopal effect in the CT26-bearing mice via the enhancement of systemic and intratumoral anti-tumor immunity.